2021
DOI: 10.1002/leg3.97
|View full text |Cite
|
Sign up to set email alerts
|

Pea and lentil flour quality as affected by roller milling configuration

Abstract: This study examined the effects of roller mill configuration on pulse flour quality.Dehulled yellow pea and green lentil were ground to flour using a laboratory roller mill characterized by its flexibility to control particle size reduction while maintaining a constant feed rate. The milling diagram length (long, six passes vs. short, four passes) and sieve sizes (large, 300 μm vs. tight, 180/150 μm) were adjusted for a total of four milling configurations. Each flour stream was characterized with respect to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(37 reference statements)
3
3
0
Order By: Relevance
“…Even though there is statistically significant difference (p ≤ 0.05) between protein, fat, and carbohydrates, the variation can be considered to be negligible in a practical industry setting. The proximate composition of yellow pea flour was in concordance with the values of de-husked yellow pea flour obtained through roller milling by Motte et al [33]. The protein values of yellow pea flours ranged from 21.25 to 22.03%.…”
Section: Yellow Pea Flour Qualitysupporting
confidence: 87%
“…Even though there is statistically significant difference (p ≤ 0.05) between protein, fat, and carbohydrates, the variation can be considered to be negligible in a practical industry setting. The proximate composition of yellow pea flour was in concordance with the values of de-husked yellow pea flour obtained through roller milling by Motte et al [33]. The protein values of yellow pea flours ranged from 21.25 to 22.03%.…”
Section: Yellow Pea Flour Qualitysupporting
confidence: 87%
“…The contents of crude protein, total starch, free glucose, and the amylose content measured by the Con A method of pea flours are shown in Table 1. The protein content of these nine peas varied from 22.7% (P1116) to 26% (Greenrich, Bibao, and Limerick), which is consistent to protein content previously reported (21.3%-26.8%) (Motte et al, 2021;Ren et al, 2021). On average, the marrowfat peas had a similar protein content (25.5%) to the green peas (25.5%), and both were slightly higher than that of yellow peas (23.8%) (p < 0.05).…”
Section: Chemical Compositionsupporting
confidence: 90%
“…Ren et al (2021) indicated that, due to the high amylose content, pulse starches generally display lower PV and BD viscosity but higher FV and SB viscosity in comparison with normal maize and tapioca starches, which is supported by the results in the current study. Pasting properties are mainly attributes of the starch component and were also reported to be significantly affected by both chemical and physical parameters and thus a comprehensive multiparameter for evaluation of the functionality of pulse flour (Motte et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Singh et al [30], days to maturity was a major yield and yield contributing character in field pea. Motte et al [31] studied on the correlation between yield and yield components of a pea.…”
Section: Days To Maturitymentioning
confidence: 99%